Peran Struktur Tata Kelola Internal dalam Meningkatkan Efisiensi Modal Intelektual di Perbankan Syariah - Chaidir, Mohammad; Kasih, Ekawahyu (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
This study aims to analyze the role of internal governance structures in enhancing intellectual capital efficiency in Islamic banking using the stakeholder theory approach. The method employed is a qualitative literature review by analyzing eight previous studies related to internal governance and intellectual capital. The results indicate that an effective internal governance structure, including the role of the Sharia Supervisory Board, accountability, transparency, and inclusive management, significantly enhances human capital, structural capital, and relational capital. Strong governance enables Islamic banking to improve competitiveness, operational efficiency, and sustainability. Additionally, investments in employee training, technology-driven Sharia innovations, and stakeholder relationship management are critical factors in optimizing intellectual capital. However, the limitations of this study include reliance on secondary data, a focus on specific regions, and a lack of quantitative analysis. This study contributes theoretically by emphasizing the importance of stakeholder-based governance in driving intellectual capital efficiency in Islamic banking.